Elements of good pharmaceutical practice in the implementation of pharmaceutical care for patients with diabetes during the martial law - I. O. Vlasenko; O. О. Komarida; L. L. Davtian (Фармацевтичний журнал, 2022)
During the martial law, the role of pharmacists increases, but they must be educated for such activities. It will ensure pharmaceutical care according to Good Pharmacy Practice. Currently, there are no developed standards for the provision of pharmaceutical care to patients with diabetes mellitus (DM) during the martial law.